2016
DOI: 10.1111/jop.12431
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary microarray assay of the miRNA expression signatures in buccal mucosa of oral submucous fibrosis patients

Abstract: This study shows that miRNA chip can be used for high-throughput screening of miRNA. Target prediction and annotation of the miRNAs demonstrated that the binding, metabolic process, molecular, and cellular process are the most common functions of the predicted targets of these newly identified miRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 13 publications
(18 reference statements)
0
27
0
Order By: Relevance
“…However, up to now, only a few of miRNAs have been reported to participate in the occurrence and development process of OSF. Chickooree et al performed a preliminary microarray analysis of miRNA expression profile to filter out 11 differential expressed miRNA in OSF (Chickooree et al, ; Zheng et al, ). Zheng et al found that miR‐203 could inhibit the arecoline‐induced epithelial–mesenchymal transition in OSF (Zheng et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, up to now, only a few of miRNAs have been reported to participate in the occurrence and development process of OSF. Chickooree et al performed a preliminary microarray analysis of miRNA expression profile to filter out 11 differential expressed miRNA in OSF (Chickooree et al, ; Zheng et al, ). Zheng et al found that miR‐203 could inhibit the arecoline‐induced epithelial–mesenchymal transition in OSF (Zheng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Oral submucous fibrosis is a well-known fibrosis lesion in oral mucosa, which carries a significantly high transformation rate of 3%-19% to oral squamous cell carcinoma (OSCC) (Ila, Girish, & Paturu, 2016;Ranganathan & Kavitha, 2011). nary microarray analysis of miRNA expression profile to filter out 11 differential expressed miRNA in OSF (Chickooree et al, 2016;Zheng et al, 2015). Zheng et al found that miR-203 could inhibit the arecoline-induced epithelial-mesenchymal transition in OSF (Zheng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that miR-4792 is downregulated in nasopharyngeal carcinoma, uterine leiomyoma, during submucosal brosis and in glioblastoma-in ltrating CD14 + cells. In contrast, miR-4792 is upregulated in glioma microvesicles [13][14][15][16][17]. Our previous studies have shown that the expression of miR-4792 increases in THP-1 cells infected with C.neoformans (WM148) ( Fig.…”
Section: Mir-4792 and Egfr Expression In Bv2 Cells Induced By C Neofmentioning
confidence: 90%
“…It has been shown that miR-4792 is downregulated in nasopharyngeal carcinoma, uterine leiomyoma, during submucosal fibrosis and in glioblastoma-infiltrating CD14 + cells. In contrast, miR-4792 is upregulated in glioma microvesicles [13][14][15][16][17]. Our previous studies have shown that the expression of miR-4792 increases in THP-1 cells infected with C.neoformans (WM148) ( Fig.…”
Section: Mir-4792 and Egfr Expression In Bv2 Cells Induced By C Neofmentioning
confidence: 90%